Readings in land reforms - Ashokvardhan, C. (Mussoorie, 2003)
The author of 'Readings in Land Reforms' literature on land reforms is noteworthy and he has been associated with the Lal Bahadur Shastri National Academy of Administration. The officer trainees in the Academy at Mussoorie and the state training institutes have enormously benefitted by his presentations, founded as they are on empirical strength and conviction. The Ministry of Rural Development, GOI has also in honoured him by inducting him in numerous expert groups on land reforms.
Keywords: Land reforms - India